A Combinatorial Description of Certain Polynomials Related to the XYZ Spin Chain. II. The Polynomials ₙ - Hietala, Linnea (Symmetry, Integrability and Geometry: Methods and Applications, 2022)
By specializing the parameters in the partition function of the 8VSOS model with domain wall boundary conditions and diagonal reflecting end, we find connections between the three-color model and certain polynomials ₙ(), which are conjectured to be equal to certain polynomials of Bazhanov and Mangazeev, appearing in the eigenvectors of the Hamiltonian of the supersymmetric XYZ spin chain. This article is a continuation of a previous paper where we investigated the related polynomials ₙ(), also conjectured to be equal to polynomials of Bazhanov and Mangazeev, appearing in the eigenvectors of the supersymmetric XYZ spin chain.